The Clash of Society and Community: The Irish Police on Screen - Brian McIlroy (Review of Irish Studies in Europe)
One can view the history of the Irish state, or states, through the police, their actions, their roles, and their struggles, and these sets of challenges provide a background for screenwriters and filmmakers who must decide on the nature of representations of policing in their work, decisions that have served to illuminate the crisis of authority at specific historical turning points. The media works in part as a societal construct that mimics community. However, when that media construct involves the police as content, we are presented with the equivalent of an uncovered wound in the body politic. The governing pretence that society is community is exposed for scrutiny.